Towards a patient-specific estimation of intra-operative femoral fracture risk. Issue 12 (10th September 2018) - Esposito, L.; Bifulco, P.; Gargiulo, P.; Gíslason, M.K.; Cesarelli, M.; Iuppariello, L.; Jónsson, H.; Cutolo, A.; Fraldi, M.
Abstract: Total Hip Arthroplasty requires pre-surgical evaluation between un-cemented and cemented prostheses. A Patient with intra-operative periprosthetic fracture and another with a successful outcome were recruited, and their finite element models were constructed by processing CT data, assuming elastic-plastic behavior of the bone as function of the local density. To resemble the insertion of the prosthesis into the femur, a fictitious thermal dilatation is applied to the broach volume. Strain-based fracture risk factor is estimated, depicting results in terms of the total mechanical strain expressed using a simple "traffic lights" color code to provide immediate, concise, and intelligible pre-operative information to surgeons.